2019
DOI: 10.1186/s12891-019-2465-8
|View full text |Cite
|
Sign up to set email alerts
|

Educational inequalities in mortality associated with rheumatoid arthritis and other musculoskeletal disorders in Sweden

Abstract: Background Musculoskeletal (MSK) disorders are less likely to be reported as an underlying cause of death (UCD) and since cause of death studies are generally limited to the UCD, little is known about socioeconomic inequalities in MSK disorders as cause of death in the general population. Using multiple-cause-of-death data, we aimed to quantify and compare educational inequalities in musculoskeletal (MSK) disorders- with non-MSK disorders-related mortality. Methods All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
1
7
0
2
Order By: Relevance
“…The lack of inequalities in SpA is in line with a previous study in the Skåne region that reported no socioeconomic differences in the risk of being diagnosed with SpA (24). While not directly comparable, our findings on associations between SSDs and the risk of chronic rheumatic diseases were generally consistent with previous studies (4,25–30). However, we revealed substantial heterogeneities in sociodemographic inequalities in chronic rheumatic diseases that have been overlooked in previous research.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The lack of inequalities in SpA is in line with a previous study in the Skåne region that reported no socioeconomic differences in the risk of being diagnosed with SpA (24). While not directly comparable, our findings on associations between SSDs and the risk of chronic rheumatic diseases were generally consistent with previous studies (4,25–30). However, we revealed substantial heterogeneities in sociodemographic inequalities in chronic rheumatic diseases that have been overlooked in previous research.…”
Section: Discussionsupporting
confidence: 92%
“…Chronic rheumatic diseases are among the leading causes of disability globally, entailing a huge health and economic burden on individuals and societies (1,2). The burden of chronic rheumatic diseases, however, is unequally distributed along social status dimensions (SSDs) such as sex, ethnicity, and socioeconomic status (3)(4)(5). The common approach in health inequalities literature (including studies on chronic rheumatic diseases) is to investigate different SSDs in isolation from one another or to treat them as additive distinct processes (6).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of MSDs was highest in miners with junior middle school education and below, and the prevalence decreased with the increase of education level. Kiadaliri et al [ 52 ] drew similar conclusions. Miners with lower education levels are generally engaged in heavy physical labor underground, and their labor intensity is higher than that of other workers working underground, so they are more prone to muscle fatigue and injury, leading to a higher prevalence of MSDs.…”
Section: Discussionmentioning
confidence: 59%
“…La importancia de la educación en pacientes con AR es considerada una herramienta complementaria en el tratamiento donde bajo las guías del ACR/EULAR 45 . De igual forma, se encuentra relación inversa entre el nivel de educación y la mortalidad por AR, las tasas de mortalidad por AR fueron 2 a 3 veces más altas en personas con nivel educativo bajo 46 .…”
Section: Discussionunclassified